2021
DOI: 10.23960/j.hptt.22182-90
|View full text |Cite
|
Sign up to set email alerts
|

Cross Application of Entomopathogenic Fungi Raw Secondary Metabolites for Controlling Fusarium Wilt of Chili Seedlings

Abstract: The research aimed to determine the effect of entomopathogenic fungi raw secondary metabolites on fusarium wilt on chili plants and on growth of chili. In vitro test used a Completely Randomized Design with 5 treatments and 5 replicate and in planta using a Randomized Block Design with 5 treatments and 5 replicatie including control, secondary metabolites of Beauveria bassiana B10, B. bassiana B16, Metarhizium anisopliae M16, dan Lecanicillium lecanii L16. Variables observed included inhibition ability, incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…In a related study, Mantzoukas et al (2022) demonstrated the remarkable reduction in aphid populations achieved by Metarhizium brunneum at a concentration of 1 × 10 8 conidia/mL. Furthermore, Soesanto et al (2021) emphasized the role of secondary metabolites from entomopathogenic fungi in mitigating infections of Fusarium oxysporum f.sp. capsici in chili plants.…”
Section: Chili Disease Management Using Biocontrol Agentmentioning
confidence: 92%
See 1 more Smart Citation
“…In a related study, Mantzoukas et al (2022) demonstrated the remarkable reduction in aphid populations achieved by Metarhizium brunneum at a concentration of 1 × 10 8 conidia/mL. Furthermore, Soesanto et al (2021) emphasized the role of secondary metabolites from entomopathogenic fungi in mitigating infections of Fusarium oxysporum f.sp. capsici in chili plants.…”
Section: Chili Disease Management Using Biocontrol Agentmentioning
confidence: 92%
“…capsici in chili plants at more than 48 %. Soesanto et al (2021) Beauveria bassiana Thrips ( Scirtothrips dorsalis ) and mites ( Polyphagotarsonemus latus ) The LC50 values against S. dorsalis and P. latus revealed that the B. bassiana formulation exhibited the highest virulence, with the lowest LC50 values recorded at 1.58 × 10 5 and 5.20 × 10 6 spores mL −1 , respectively. Murugasridevi et al (2021) Metarhizium anisopliae Viruses The secondary metabolites from M. anisopliae demonstrated strong disease suppression by reducing the incubation period, viral disease intensity, and AUDPC by 34.22 %, 77.98 %, and 79.49 %, respectively.…”
Section: Chili Disease Management Using Biocontrol Agentmentioning
confidence: 99%